Development of the Storm‐Induced Ionospheric Irregularities at Equatorial and Middle Latitudes During the 25–26 August 2018 Geomagnetic Storm - Iurii Cherniak; Irina Zakharenkova (Space Weather)
Abstract Can geomagnetic storms during low solar activity trigger formation of extreme equatorial plasma bubbles (EPBs) that affect low and midlatitudes? We analyzed the ionospheric response to the 25–26 August 2018 geomagnetic storm and revealed formation of intense ionospheric plasma irregularities over broad latitudinal ranges from equatorial toward middle latitudes in the American and Pacific sectors. Storm‐induced penetration electric fields created favorable conditions for strong fountain effect uplifted the equatorial ionosphere, enhancement of the equatorial ionization anomaly (EIA), and postsunset EPBs generation. We found two patterns of equatorial ionospheric irregularities expansion toward low and middle latitudes: (a) storm‐induced EPBs developed over a large latitudinal extent between widely spread EIA crests, (b) narrow channel of the ionospheric irregularities stretched away from the EPB location toward the auroral zone in the northwestward direction. The EPBs latitudinal extent largely exceeded climatological‐based expectations for solar minimum conditions; EPBs reached atypically high latitudes (20°–25° magnetic latitude [MLAT]) in the Pacific Ocean sector. The poleward‐streaming plasma density depletions were registered along the western coast of North America. The ionospheric irregularities transported in the northwestward direction toward midlatitudes reaching as high as 40°–45° MLAT. The passage of these ionospheric irregularities coincided with the spread‐F conditions recorded at a midlatitude ionosonde (42° MLAT)—rather atypical phenomenon for midlatitudes. It is suggested that enhanced westward drifts associated with prompt penetration and Sub Auroral Polarization Stream electric fields can support the northwestward plasma transportation.